Effects of wide‐range γ‐irradiation doses on the structures and properties of 4, 4′‐dicyclohexyl methane diisocyanate based poly(carbonate urethane)s. Issue 22 (1st July 2014) - Zhang, Chen; Jiang, Xiujuan; Zhao, Zhiyang; Mao, Lixin; Zhang, Liqun; Coates, Phil
<x xml:space="preserve">Abstract</x> For medical applications, 4, 4′‐dicyclohexyl methane diisocyanate (HMDI)‐based poly(carbonate urethane)s were synthesized from HMDI and 1, 4‐butanediol as hard segments and poly(carbonate diol) (number‐average molecular weight = 2000 g/mol) as soft segments. The effects of wide‐range γ irradiation on the samples were examined through a series of analytical techniques. Scanning electron microscopy revealed that γ irradiation etched and roughened the surfaces of the irradiated samples. The gel content and crosslinking density measurements confirmed that crosslinking occurred along with degradation at all of the investigated irradiation doses and the degree of both crosslinking and degradation increased with increasing irradiation dose. Fourier transform infrared spectroscopy demonstrated that chain scission in the γ‐irradiated samples occurred at the carbonate and urethane bonds. The decreasing molecular weight and tensile strength indicated that the degradation increased with the γ‐irradiation dose. Differential scanning calorimetry and dynamic mechanical thermal analysis indicated that γ irradiation had no significant effect on the phase‐separation structures. There was a slight reduction in the contact angle. An evaluation of the cytotoxicity demonstrated the nontoxicity of the nonirradiated and irradiated polyurethanes. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 41049.